PENGARUH PENERAPAN ISO 9001:2008 TERHADAP KINERJA PEGAWAI SEKRETARIAT DAERAH PEMERINTAHAN KOTA MALANG - Pamungkas, Septantya Chandra; Thoyib, Armanu (Jurnal Ilmiah Mahasiswa FEB, 2013)
The biggest challenge for organizations which are engange in the global service systems, which provides freedom of speech, is how to meet the desired standards of service by the customers. Similarly for the government agencies that provide services to the public. To be recognized as an organization that conform the requirement for quality, organization implemented Quality Management System (QMS) ISO 9001:2008. QMS ISO 9001:2008 believed to be able to give positive encouragement to employees to improve performance continuously. This research aimed to determine the effect of the application of QMS ISO 9001:2008 on Sekretariat Pemerintah Kota Malang’s employee performance. The research method is explanatory research with the aim of explaining the relationship between variables through hypothesis test. The results showed that partially Human Resources (X1), Work Infrastructure (X2), and Work Environment (X3) in QMS ISO 9001:2008 has positive and significant impact on Sekretariat Pemerintah Kota Malang’s employee performance. Simultaneously, these variables are has positive and significant impact on Sekretariat Pemerintah Kota Malang’s employee performance as well. Work Environment Variables (X3) is the most dominant variable which influences on employee performance (Y). Based on this research, it can be concluded that the implementation of QMS ISO 9001:2008 has positive effects in effort to improve employee performance. Keywords: ISO 9001:2008, Human Resources, Work Infrastructure, Work Environment, Employee Performance.